L. Frank Baum's The wonderful Wizard of Oz - Hautzig, Deborah; Robinson, Robin, 1986-; Baum, L. Frank (Lyman Frank), 1856-1919. (New York, New York : Penguin Young Readers, an imprint of Penguin Group (USA) Inc., 2013)
After a cyclone transports her to the land of Oz, Dorothy must seek out the great Wizard in order to return to Kansas.
edited hb 2015-06-16
Keywords: Fantasy; Oz (Imaginary place) -- Juvenile fiction; Wizards -- Juvenile fiction; Fantasy fiction